Questions of travail: Travel, culture, and nature in the poetry of Anne Bradstreet, Elizabeth Bishop, and Amy Clampitt - Boschman, Robert (My University, 1999)
This study examines the work of three American poets, Anne Bradstreet (1612-1672), Elizabeth Bishop (1911-1979), and Amy Clampitt (1920-1994). Besides the thematic strands of culture and nature, the thesis presents travel, geography, and cartography as underlying metaphors for the processes by which European culture has transplanted itself to this continent. Obviously Anne Bradstreet thought about travel and geography as she set out for the New World in 1630 at the age of eighteen. The English Puritan culture that encodes itself in Bradstreet's poems often reveals how she imagines her own distance from England. Such an engagement also makes Elizabeth Bishop central. Not only does she focus extensively on the themes of travel and geography, but for her such preoccupations stem from a disrupted childhood that made it continually necessary to redefine "home" throughout adult life. Amy Clampitt is also constantly moving about the globe in ways that make the metaphor of travel significant and intriguing. Like Bradstreet and Bishop, Clampitt imagines the landscape as a living organism subject to the actions of humankind, and like them she looks back on a ruptured early personal history.
While I have attempted to take an individualistic approach with each of Bradstreet, Bishop, and Clampitt, I have also continually sought to disclose the important ways in which their oeuvres are related. Thus while the chapters on Bradstreet refer the reader to the extensive critical and historical work already extant concerning both her and her community, those on Bishop similarly allude to her rich association with the work of Charles Darwin, particularly his The Voyage of the Beagle (1836). Clampitt, likewise, looks to Darwin in a no-less important way, although I have also regarded her work on the intersections between nature and culture as akin to that of Annie Dillard. Like Dillard, Clampitt has invited God back into the discourse, taking a step otherwise too problematic for the likes of Bishop. Indeed, the deity so integral to the Puritan interpretation of the environment closely examined in the chapters on Bradstreet cannot be reintroduced without raising serious issues relating to nature.
Keywords: English Language and Literature; English Language and Literature